The Evolution of Looks and Expectations of Asian Eyelid and Eye Appearance - Fakhro, Abdulla; Yim, Hyung Woo; Kim, Yong Kyu; Nguyen, Anh H. (Seminars in Plastic Surgery, 2015)
Since Mikamo developed the double blepharoplasty technique at the end of the 19th century, there has been significant developments in the idealized periorbital appearance of the Asian patient. Currently there are four potential vectors of change possible (upper, lower, medial, and lateral). South Korea is the only country that most often utilizes the change in all four vectors. There is additionally a stark contrast between Asia-based and Western-based approach to the Asian eyes. In Asia, outside of South Korea, many surgeries employ a combined vertical upward vector and a medial directional change, particularly for the young eyes. In Western-based approaches, Asian blepharoplasty remains at this time primarily an open incision, upward vector change.
Keywords: Asian blepharoplasty; lateral canthoplasty; double eyelid surgery; medial epicanthoplasty; epicanthus; Mongolian fold; aegyo-sal love band